The Fundamental Principles of Zoltan Bakonii’s Artistic and Educational Activities - Alina Voloschuk (Pedagogical Discourse, 2015)
The article is based on a synthesis analyzes of the conceptual principles that guided in the education of youth by means of the fine art artist and educator Zoltan Bakonii. Consideration of conceptual foundations showed deep mastering and comprehension of Zoltan Bakonii’s pedagogical inheritance of prominent thinkers in history of pedagogics. Quite a bit ideas, thoughts, positions were conscious acceptance of the advanced views of domestic teachers. It is traced how conceptual principles, being traditional, at the same time, acquired creative development and innovative realization in Zoltan Bakonii’s activity. Attention is accented on the fact that, approved by the time, positively perceived by other teachers ideas, the principles of Zoltan Bakonii, have been considered relevant to modern domestic out-of-school artistic education.